Treatment decision for impacted mandibular third molars: Effects of cone-beam computed tomography and level of surgeons' experience. - Emine Adali; Meltem Ozden Yuce; Gözde Işik; Elif Şener; Ali Mert (PLoS ONE)
The aim of this study was to analyse the effect of surgeons' experience and the benefit of using cone-beam computed tomography (CBCT) images, compared to the use of panoramic radiography (PAN) images, on their decisions with regard to mandibular third molar treatment modality. Panoramic radiographs and CBCTs from a total of 143 patients who had undergone impacted third molar surgery were randomly evaluated for treatment decision by 10 participants with differing clinical experience (5 novices and 5 experienced surgeons). The degree of agreement between the same type of participants was 'Substantial Agreement' (0.61-0.80) or 'Almost Perfect' (0.81-1.00). When the treatment modality decisions of the experienced and novice surgeons, using PAN and CBCT images, were compared, a statistically significant difference was found (p<0.01) between the variables. In 50 cases, experienced surgeons decided from CBCT images that total extraction was the best treatment method but opted for coronectomy when presented with PAN images of the same cases. In 164 cases novice surgeons decided on total extraction from CBCT images but chose coronectomy when presented with PAN images of the same cases. The results obtained from this study revealed that the degree of professional experience of the surgeon was a significant factor in determining the treatment decision. Moreover, the treatment choice of experienced surgeons was less affected by the change in imaging technique employed, when compared to novice surgeons.